Hellenistic history and culture - Green, Peter, 1924- (Hellenistic culture and society ;, 1993)
In a 1988 conference, American and British scholars unexpectedly discovered that their ideas were converging in ways that formed a new picture of the variegated Hellenistic mosaic. That picture emerges in these essays and eloquently displays the breadth of modern interest in the Hellenistic Age. A distrust of all ideologies has altered old views of ancient political structures, and feminism has also changed earlier assessments. The current emphasis on multiculturalism has consciously deemphasized the Western, Greco-Roman tradition, and Nubians, Bactrians, and other subject peoples of the time are receiving attention in their own right, not just as recipients of Greco-Roman culture. History, like Herakleitos' river, never stands still. These essays share a collective sense of discovery and a sparking of new ideas - they are a welcome beginning to the reexploration of a fascinatingly complex age.